(untitled) (Research, Society and Development, 2022)
A Literature Review was carried out from 2011 to 2021 through Bibliographic Research aiming to update the state of the art on self-medication of the elderly population and the role of the pharmacist. The research was carried out in the PubMed/Medline, SciELO, LILACS and Google Scholar databases, using the following health descriptors: self-medication, self-administration, adverse effects, medication consumption habits, medicines, pharmacist, pharmaceutical care, elderly and people old woman. In general, it was possible to perceive that the research found in the initial searches, had as objective the investigation of self-medication in a very comprehensive way, in the most diverse strata of the Brazilian population, however, the present research was restricted to the elderly population that indiscriminately uses medicines for the relief of symptoms, their pain and in the search for a cure for their age-related comorbidities, as well as, culturally, they share medicines with the family or circle of friends, uses the leftovers of medicines found at home that often fail to comply professional prescription. Therefore, it can be said that self-medication is a practice considered to be avoidable, so it is believed that programs aimed at the education of the elderly can contribute to actions aimed at clarifying the elderly population in relation to the rational use of medicines, thus highlighting the importance of the role of pharmacists who are responsible for the control, guidance and prevention of self-medication, the risks and benefits of the elderly in indiscriminately consuming any medication, especially those exempt from prescription.